If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -1c = -2c Solving 7 + -1c = -2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '2c' to each side of the equation. 7 + -1c + 2c = -2c + 2c Combine like terms: -1c + 2c = 1c 7 + 1c = -2c + 2c Combine like terms: -2c + 2c = 0 7 + 1c = 0 Add '-7' to each side of the equation. 7 + -7 + 1c = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 1c = 0 + -7 1c = 0 + -7 Combine like terms: 0 + -7 = -7 1c = -7 Divide each side by '1'. c = -7 Simplifying c = -7
| (18x^2)-43x+17=0 | | 24x+33+14x=162 | | 12z=208 | | 3/4n+11=5 | | 10-6=34-5d | | 0.8+x=1.5 | | 2x+2x+2=4+2x | | factor(x+8)(x-2)=-21 | | -3x-3=x+3 | | (-18x^2)+43x-17=0 | | 10-7x+11x=-2(-4x+1) | | -8+8a-5-10=7a-11 | | (108x^2)-258x+102=0 | | 4n+2(3n-5)-8+n= | | 13-7n=62 | | 5x-8=5(x+6) | | 7(x+3)=5x-19 | | 12x-8x=-4x+4 | | 7k+16=2 | | 9x+5=-12x-16 | | 6y-6y=8 | | x^2dy+y^2dx=0 | | 5(2x-4)=x+7 | | 8-4(6x-4)=34 | | 2(x+5)-10=40 | | 10+2n=28 | | 0=y-7x+5 | | -3+3x=5+x | | (4x-2z)(4x+2z)= | | 5x^3-x^2-125x+25=0 | | 5x-9x+54=5x+36 | | -6x-2y=22 |